O Pão Que o Viado Amassou: semiotic contribution to natural language processing - Silva, Tulio Ferreira Leite da (Estudos Semióticos, 2022)
The growing production of data on the internet and digital social  networks is unavoidable and, by 2025, humanity is expected to produce 463  exabytes of data per day. The size of such a value can be illustrated with the  image of approximately half a trillion of 1 gigabyte flash drives. This  phenomenon, however, far from being a cause for celebration (as Big Tech  wants), has been directly responsible for countless evils to society and  democracy: hate speech and disinformation are just the tip of the iceberg. Due  to this alarming scenario, conducting research on the intersection between  Semiotics and data processing technologies is urgent. In this paper, we intend  to briefly present the scenario of one of the most celebrated areas of Artificial  Intelligence (characterized by artificial neural networks) and then use the  concepts of situational context and discursive competence to debate the  mechanisms of signaling biased discourses, used to mark digital publications  with the potential for disinformation or hate speech. An iconic case that we  intend to focus on, O pão que o viado amassou is a delivery from Curitiba,  created by a good-natured gay man, who was penalized by Facebook.